POTENSI WAKAF UANG DI ERA DIGITAL MELALUI KONSEP PENGEMBANGAN DAN PEMBERDAYAAN EKONOMI ISLAM DI INDONESIA - Ika Milyana, Baiq Santi Mardianti; M. Zaidi Abdad; Nikmatullah (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2025)
This paper aims to answer questions about the potential of cash waqf in the digital era through the concept of developing and empowering Islamic economics in Indonesia. The research conducted is a library research. The main sources of law in this study are the Al-Quran (Qur'an Surah. Al-Hadid: 18), (Qur'an Surah. Ali Imran: 92), (Qur'an Surah. Al-Baqarah: 267), and the Hadith narrated by Muslim from Abu Hurairah, and regulated in Law Number 41 of 2004 and Government Regulation Number 42 of 2006 concerning Waqf. The concept of cash waqf basically involves the transfer of assets by the wakif to be managed and utilized for the benefit and welfare of the community. The potential of cash waqf can be maximized if a nadzir is able to manage it effectively. Data analysis on cash waqf shows its contribution to social welfare, and since then, the practice of cash waqf has grown and become widely known in society. Amidst technological advances and the phenomenon of digitalization, the process of managing cash waqf has also accelerated. Currently, waqf can be done anytime and anywhere, and is given for various community empowerment purposes, such as in the fields of education, health, social, and economics